2009
DOI: 10.1124/mol.109.055947
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Nucleolin Is a Receptor for the Anticancer Aptamer AS1411 in MV4-11 Leukemia Cells

Abstract: AS1411 is a DNA aptamer that is in phase II clinical trials for relapsed or refractory acute myeloid leukemia and for renal cell carcinoma. AS1411 binds to nucleolin, a protein that is overexpressed in the cytoplasm and on the plasma membrane of some tumor cells compared with normal cells. Studies were performed to determine whether cell surface nucleolin is a receptor for AS1411 in the acute myeloid leukemia cell line MV4-11. Biotinylation of MV4-11 cell surface proteins followed by immunoblotting of the biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
159
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(165 citation statements)
references
References 25 publications
5
159
0
1
Order By: Relevance
“…Recent studies showed that nucleolin, a nuclear protein, was present on the surface of various cell types, despite lacking a transmembrane domain or a signal sequence (24,25). Therefore, nucleolin acts as a receptor on plasma membrane and shuttles the ligand from the plasma membrane to the cytoplasm and nucleus (24,26). Likewise, KLF4 may also migrate to the cell surface and act as a kallistatin-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that nucleolin, a nuclear protein, was present on the surface of various cell types, despite lacking a transmembrane domain or a signal sequence (24,25). Therefore, nucleolin acts as a receptor on plasma membrane and shuttles the ligand from the plasma membrane to the cytoplasm and nucleus (24,26). Likewise, KLF4 may also migrate to the cell surface and act as a kallistatin-binding protein.…”
Section: Discussionmentioning
confidence: 99%
“…The widely demonstrated role of NCL in tumorigenesis suggests that inhibition of its oncogenic actions reduces tumor aggressiveness (9,13,19,24,32,34,47), and several studies have proposed NCL as an ideal target for antineoplastic therapies in different solid and hematological malignancies (9,19,25,34,37,38,41,42,48,49). Given the selective presence of NCL on cancer cells and cancer-associated endothelial cells, but not on normal cells, molecules targeting NCL might represent an effective approach for the selective delivery of drugs or toxins to tumors while minimizing side effects (25,41).…”
Section: Discussionmentioning
confidence: 99%
“…NCL is able to shuttle between the cell surface and the cytoplasm of cancer cells (32,34), a property that makes NCL an attractive target for the selective delivery of antineoplastic drugs or prodrugs, leaving normal cells unaffected (25).…”
Section: Significancementioning
confidence: 99%
“…It controls the metabolism of DNA and RNA in the nucleolus (44,45), shuttles proteins into the nucleus (46), provides posttranscriptional regulation of strategic mRNAs in the cytoplasm (47,48), and serves as a ligand for proteins, such as midkine and the heparin-binding growth-associated molecule, on the cell surface (49). NCL is also involved in the proliferation of many types of cancer (34,(50)(51)(52) and serves as a prognosis marker and therapeutic target for cancer treatment (53)(54)(55). Furthermore, NCL also participates in the pathogenic mechanism and mediates the replication of several viruses and/or serves as a cell surface receptor for Escherichia coli O157 (56), Helicobacter pylori (57), RSV (28), adeno-associated virus type-2 (AAV-2) (58), coxsackie B virus (59), and HIV (29).…”
Section: Discussionmentioning
confidence: 99%